2017
DOI: 10.1177/2042018817731073
|View full text |Cite
|
Sign up to set email alerts
|

Visfatin level in children and adolescents with autoimmune thyroiditis

Abstract: Background: This study aims to assess the levels of visfatin in children and adolescents with autoimmune thyroiditis (AIT) and its relationship with disease-related variables. Methods: The study included 84 children and adolescents with AIT and 84 healthy subjects. Measurements of fasting glucose, insulin, thyroid-stimulating hormone (TSH), free thyroxin (FT4), antithyroid peroxidase antibodies (TPOAb) and antithyroglobulin antibody (TgAb) were completed, with assessment of visfatin levels. Results: Overt hypo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
5
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 29 publications
1
5
2
Order By: Relevance
“…body mass index, waist-to-hip ratio, or skin fold) (25,26). We have confirmed our previous findings that serum visfatin correlates with TPOAbs in hypothyroid patients, which has been recently also reported in children (27). Likewise, Caixas at al.…”
Section: Discussionsupporting
confidence: 92%
“…body mass index, waist-to-hip ratio, or skin fold) (25,26). We have confirmed our previous findings that serum visfatin correlates with TPOAbs in hypothyroid patients, which has been recently also reported in children (27). Likewise, Caixas at al.…”
Section: Discussionsupporting
confidence: 92%
“…In previous studies, circulating visfatin levels in T1DM were higher [80,81] or lower [82][83][84] compared to healthy controls. Recent studies have suggested a relationship between increased visfatin levels and chronic autoimmune thyroiditis [78,85]. Our study showed non-significantly lower serum levels of visfatin in women with T1DM compared with women in the control group.…”
Section: Discussioncontrasting
confidence: 47%
“…Based on previous studies, visfatin has been identified as a potential biomarker of insulin resistance, obesity, metabolic syndrome, type 2 diabetes mellitus, and CV disease [76]. Moreover, recent reports have indicated its association with the development of inflammation in autoim-mune inflammatory disorders [20,[77][78][79]. However, results concerning visfatin in T1DM and/or HD are limited and conflicting.…”
Section: Discussionmentioning
confidence: 99%
“…Visfatin is also thought to have anti-inflammatory properties. Interestingly its levels have been found to be elevated in several autoimmune conditions including thyroiditis and arthritis, 40,41 where it has been suggested that it may be induced in response to inflammation, possibly serving as a "negative feed-back" loop aimed at acquiescing inflammation. We also note that the adipokine abnormalities we identified in children with MS compared to the disease controls might reflect differences between recurrent/ongoing versus monophasic disease activity.…”
Section: Discussionmentioning
confidence: 99%